Teaching primary care physicians the 5 A's for discussing weight with overweight and obese adolescents. Issue 10 (October 2016) - Pollak, Kathryn I.; Tulsky, James A.; Bravender, Terrill; Østbye, Truls; Lyna, Pauline; Dolor, Rowena J.; Coffman, Cynthia J.; Bilheimer, Alicia; Lin, Pao-Hwa; Farrell, David; Bodner, Michael E.; Alexander, Stewart C.
Highlights: Physician use of 5 A's shows promise for encouraging weight-related changes. A 60-min tailored, online intervention improved physician use of the 5 A's. Teaching physicians can help adolescents attain a healthy weight. Abstract: Objective: We developed an online intervention to teach physicians both MI (addressed in outcomes paper) and the 5 A's (Ask, Advise, Assess, Assist, and Arrange) when discussing weight with overweight/obese adolescents. Methods: We audio recorded 527 encounters between adolescents and physicians and coded the 5 A's during weight/BMI discussions. Half of physicians were randomized to receive a tailored, intervention that included their own audio-recorded clips. To examine arm differences, we used multilevel linear mixed-effects models for sum of 5 A's and generalized estimating equations (GEE) models with a logit link for each of the A's separately. Results: Intervention arm physicians used more A's than control physicians (estimated difference = 0.6; 95%CI(0.2, 1.0);p = 0.001). Intervention physicians used Assess (p = 0.004), Assist (p = 0.001) and Arrange (p = 0.02) more when compared to control arm physicians. Conclusion: An online intervention increased physicians' use of the 5 A's when discussing weight with overweight adolescents. These results are promising as the online intervention improved performance for the three A's that are infrequently used (Assess, Assist, and Arrange) yet have the most impact. Practice implications: A tailored online program can increase physicians' use of the 5 A's behavioral counseling approach in clinical practice with adolescents.